Accounting Information System Design for UMKM Cash Transactions: Desain Sistem Informasi Akuntansi untuk Transaksi Tunai UMKM - Evi Kurni a Fitri; Imelda Dian Rahmawati (Indonesian Journal of Law and Economics Review, 2025)
General Background Micro, small, and medium enterprises play a vital role in national economic sustainability, yet many operate without structured accounting information systems. Specific Background This condition is evident in UMKM Tahu Jaya Sentosa, where cash receipt and cash disbursement activities are conducted using simple practices without formal recording. Knowledge Gap Limited understanding and implementation of accounting information systems constrain internal control and financial transparency in UMKM operations. Aims This study aims to design an accounting information system for cash receipts and cash disbursements that can be applied as a practical guideline for UMKM. Results Using a qualitative descriptive approach through interviews and observations, the study finds that cash transactions are not recorded in journals or ledgers, internal control is informal, and financial information is not systematically documented. Novelty The study presents a context-based accounting information system design tailored to the operational realities of a small-scale UMKM. Implications The proposed design provides practical guidance for improving cash transaction recording and internal control, supporting better financial management practices in UMKM environments. Keywords: Accounting Information System, Cash Receipts, Cash Disbursements, Internal Control, UMKM Key Findings Highlights: Cash transaction activities are conducted without formal accounting records. Internal control relies on informal practices and owner experience. A structured system design offers practical guidance for UMKM financial management.